The Studies of Cholesterol Variation in Relation to the Breeding Phases of Female Tilapia, Oreochromis mossambicus (Peters) - Pathan, J. G. K.; Baile, V. V. (International Journal of Bio-resource and Stress Management, 2019)
The reproductive cycle of African multiple spawner Tilapia, Oreochromis mossambicus, is divided into preparatory, prespawning, spawning and postspawning phases, after evaluating the gonadosomatic index and percentage dominance of particular types of oocytes. In the preparatory phase GSI is 0.21887+0.021 and ovary is dominated by stage I and stage II oocytes which constitute 36.873% and 32.992% of the total oocytes respectively. Some developing oocytes of stage III (14.467%), stage IV (5.895%) and stage V (9.715%) are also observed. In the spawning phase, the ovaries are very much elongated, occupying about 2/3rd of the body cavity. They are turgid and yellow in colour holding large number of translucent eggs. Ovarian wall becomes very thin. The GSI increases to 3.24932. The ovary is dominated by stage VI follicles; which are 45.731% of the total oocyte count. Positive staining of cholesterol is observed in the ovary, as maturation proceeds. Intensity of staining increases in the ooplasm successively from stage I to stage VI oocytes. Cholesterol in nervous, endocrine and somatic tissues with respect to the ovarian cycle is ascertained by their histochemical demonstration and biochemical estimations. Brain and pituitary has highest cholesterol in prespawning phase, lowest in spawning phase. On the contrary, ovary has cholesterol is highest in the prespawning and lowest in the spawning phase. Liver and muscles show highest cholesterol in the preparatory and lowest in the spawning phase.